STUDENTS’ PERCEPTION ON SPEAKING ANXIETY IN ENGLISH CLASSROOM: PSYCHOLOGICAL VIEW - Pohan, Abi; Kusumawardany, Irene Nany (Inspiring: English Education Journal, 2023)
The world has seen significant changes as a result of globalization. As English is widely used all over the world, there is a need for learners to acquire communication skills in classrooms. Thus, learners should be able to overcome their psychological problems while learning in the classroom, such as anxiety. This study aims to investigate the student’s perception of psychological problems faced in terms of anxiety in SMPN 30 Malang. The respondents from this study are 9th-grade students in SMPN 30 Malang, which has a total number of 49 students. The data was collected from junior high school. In this study, the researcher used a descriptive qualitative study. The researcher collected the data through a questionnaire. The finding of this study shows that most of the 9th graders in SMPN 30 Malang have speaking anxiety. Test Anxiety is the most influencing factor affecting 9th graders’ speaking performance. The test anxiety was found because of their fear of failure and high pressure in their English class.